The event of Croatia's EU accession and membership from the Croatian high school students' perspective - Anamarija Pisarović; Sanja Tišma; Krševan Antun Dujmović; Mira Mileusnić Škrtić (Journal of Risk and Financial Management, 2021)
The knowledge, attitudes and perceptions of the high school students on Croatia's European Union (EU) accession event were omitted in numerous public opinion polls conducted since the 2013 accession. Therefore, the paper shows key benefits of Croatia's EU accession and the recent attitudes of high school students about the meaning of this event for their future lives. Research methods include desktop analysis regarding previous researches of the population attitudes and a quantitative survey conducted in January 2017 on a sample of a total of 1944 school graduates who were interviewed on issues of knowledge, perception and attitude to the event of Croatia's entrance and membership in the EU. The results point out that although Croatia acquires significant benefits from the EU accession, the very event is not recognized as being the key one by high school students. Considering that in many cases the youth opinion is the best indicator of overall social problems and considering the future programs and obligations as well as the role expected from the youth in implementation of these programs, the research findings on the perception of the event of Croatia's accession to the EU are a field within which future policy activities are envisaged.
Keywords: 330; knowledge; Croatia; European Union; EU accession; high school students; opinion polls